Underwater Noise During the Construction Works of the Central Terminal in Klaipėda and its Impact on Fish - Bagočius, Donatas (Jaunųjų mokslininkų darbai, 2016)
Human activities regularly carried out in the Baltic Sea area vary from the the construction of a terminal in the Klaipėda Strait to the removal of ordnance and ammunition from the seabed of the Baltic Sea. The construction works of the Central Klaipėda Terminal lasted from the spring to the summer of 2012. Steel piles that support the terminal structure were ramed into the bottom of the Strait using a vibro hammer. The level of noise during the construction works was measured and analysed. The highest level, 202.6 dB re 1µPa at 1 metre, was recorded when a double T pile was driven into the bottom. That had an ecological impact on fish migrating through the Klaipėda Strait. Fish, are sensitive to noise, they, have a complex sensory system, their hearing organs allow them to detect underwater sounds. Acoustic survey showed that the level of noise caused by vibro techniques was high and raised risk for fish migrating trough the Klaipėda Strait being affected.